O Biodireito, a Bioética: correlações com a Biopolítica em Michel Foucault - Freitas, Patrícia Marques (2018)
This study aims to analyze how Michel Foucault’s Biopolitics notion may have contributed to Biolaw and Bioethics by developing studies on eugenics and biological racism as the backbone of the relation between Biopolitics, Bioethics and Biolaw. For that, the bibliographical research method was chosen. In order to understand the meaning of Biopolitics — that is the extension of the State power controlling bodies and institutionalizing policies to discipline, regulate and rule over the aforementioned body —, Foucault’s genealogical period writings were scrutinized. This study is divided in four parts, for the sake of better understanding the research problem. The first and the second focuses on studying Michel Foucault’s Biopolitics and it was decided to start with “Dits et écrits”, volume II, translated into Portuguese, where Foucault starts criticizing the biological aspects. Then, we move to Microphysics of power, first mentioned in “Birth of Social Medicine”, when Foucault used the term Biopolitics for the first time. After that, “The Will to Knowledge”, volume I, about the History of sexuality, is used as it discusses Biopolitics further. Next, this study dives into courses taught by Foucault at Collège de France, more specifically in the course “In Defense of Society” (1976), followed by “Security, Territory, Population” (1977-1978), and, finally, “Birth of Biopolitics” (1978-1979). This way, it is shown in the end what Michel Foucault understood as Biopolitics, in a conceptual mapping in order to build the theoretical reference for this study. The third part of this work focuses on the historic journey that paved the road for Bioethics, in a way of consolidating it as part of practical philosophic ethics, related to ethical behavior of health care professionals. Biolaw is stressed by analyzing historical context when it was created and its driving principles as well. Forth part makes explicit how eugenics, which was part of Foucault’s analysis on Biopolitics — that is stated in his analysis of the degeneration theory —, and themes currently related to Biolaw and Bioethics, under the perspective of the growing human need of “race improvement”